PENGAWASAN PENCEMARAN LINGKUNGAN (STUDI KASUS LIMBAH INDUSTRI KELAPA SAWIT DI KABUPATEN INDRAGIRI HULU) - Muhammad Sulaiman; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Industrial development is now increasingly rapid which is followed by the advancement of science and technology. developments in the industrial sector also have a negative impact, namely in the form of industrial waste which if not managed properly in accordance with the SOP that has been determined will have an impact on environmental balance. Can be seen from the occurrence of problems of air pollution, water pollution, and land pollution. Considering the high potential of pollution caused by the waste of the oil palm industry, which if not properly managed by the waste, supervision is needed on the management of this industrial waste. Monitoring of industrial waste is carried out so that there are no deviations that can cause environmental pollution. The supervision at the Environmental Agency in Indragiri Hulu Regency is still not optimal. The purpose of this study is to see how the environmental pollution is monitored (a case study of palm oil industry waste in Indragiri Hulu Regency) and what are the factors that become obstacles to supervision in the Indragiri Hulu Regency Environmental Agency. This research was conducted in Indragiri Hulu Regency. The theory used in this study is the Manullang theory which has three supervisory indicators, namely setting standards, taking assessment actions, and carrying out corrective actions. The results of this study indicate that the supervision of the Department of Environment is still not optimal, the lack of socialization and the standard time in conducting direct supervision of the field which is still considered ineffective and also the factors that inhibit supervision by the Environmental Agency of Indragiri Hulu Regency are human resources, funds or costs and community participation.Keywords : Supervision, Environmental Agency